1990
DOI: 10.3758/bf03327252
|View full text |Cite
|
Sign up to set email alerts
|

The precocial mouse, Acomys cahirinus

Abstract: Acomys cahirinus (the "spiny mouse") is a member ofthe same rodent subfamily as the laboratory rat and mouse. Acomys differs from the laboratory species in several ways, including the fact that it is adapted to a semiarid lifestyle and is born after a long gestation with functional sensory and motor systems. The existing, and quite dispersed, literature on the anatomy, physiology, and behavior of Acomys is briefly reviewed.Acomys cahirinus (calIed the "spiny mouse" because of the bristly fur covering the rump … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

1995
1995
2023
2023

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(3 citation statements)
references
References 95 publications
0
3
0
Order By: Relevance
“…Estimating height depends, among others, on the reaction to depth and the ability to correctly perceive depth. Jirds are an altricial species in which the offspring depend on parental care for several weeks after birth [ 46 ], whereas spiny mice are precocial and their offspring can become independent within a few days postnatally [ 47 ]. Previous studies have revealed differences in depth perception between precocial and altricial species [ 6 , 48 50 ].…”
Section: Discussionmentioning
confidence: 99%
“…Estimating height depends, among others, on the reaction to depth and the ability to correctly perceive depth. Jirds are an altricial species in which the offspring depend on parental care for several weeks after birth [ 46 ], whereas spiny mice are precocial and their offspring can become independent within a few days postnatally [ 47 ]. Previous studies have revealed differences in depth perception between precocial and altricial species [ 6 , 48 50 ].…”
Section: Discussionmentioning
confidence: 99%
“…They also do not dwell in burrows, but shelter in the crevices between rocks and boulders. Spiny mice also differ from rats and mice in many other aspects (see [ 27 ] for review) and they differ from flatland rodents in particular in-depth perception [ 28 ], distance perception [ 29 ], exploration [ 30 , 31 , 32 ], and excitability [ 33 ]. In accordance with such differences, it was found that environments were perceived differently even by closely related species [ 34 , 35 , 36 , 37 ].…”
Section: Introductionmentioning
confidence: 99%
“…While limited information is available regarding A. cahirinus reproductive biology, recent research has highlighted several reproductive characteristics that are rare in rodents. Acomys cahirinus produce small litters with precocial young [ 4 ] and a relatively long gestation (~ 39 days; [ 5 ]), cannot become pseudopregnant [ 6 ], and, more recently, were the first rodents to exhibit a natural, human-like menstrual cycle [ 7 ] and a menopause-like transition [ 8 ]. Interestingly, unlike most rodents, A. cahirinus also do not produce a visible copulatory/seminal plug [ 9 ], which provides significant challenges when using mated females for gestational studies as ejaculation, and therefore early pregnancy, cannot be confirmed non-invasively.…”
Section: Introductionmentioning
confidence: 99%